Fear of Childbirth After Major Orthopedic Traumas: A Nationwide Multi‐Register Analysis - Vaajala, Matias; Liukkonen, Rasmus; Kuitunen, Ilari; Ponkilainen, Ville; Mattila, Ville M.; Kekki, Maiju (Birth (Berkeley, Calif.), 2025)
ABSTRACT Background The aim of this study was to evaluate the association between previous major traumas and the prevalence of fear of childbirth (FOC) and the subsequent effects of FOC on the intended mode of delivery. Methods In this nationwide retrospective register‐based cohort study, data from the Care Register for Health Care were linked with the National Medical Birth Register (MBR) to evaluate the prevalence of FOC after major traumas. A total of 18,573 pregnancies met the inclusion criteria. A multivariable logistic regression model was used to assess the effects of FOC on the intended mode of delivery. Women with major traumas before pregnancy were compared to individuals with wrist fractures. Adjusted odds ratios (aORs) with 95% CIs between the groups were compared. Results Of those pregnancies that occurred after major traumas, 785 (6.2%) women were diagnosed with FOC after traumatic brain injury (TBI), 111 (6.1%) women after spine fracture, 38 (5.0%) women after pelvic fracture, 22 (3.2%) women after hip or thigh fracture, and 399 (5.2%) women in the control group. Among those women diagnosed with FOC, the adjusted odds for elective CB as an intended mode of delivery were highest among women with previous spine fractures (aOR 2.28, CI 1.45–3.60) when compared to the control group. Conclusions We found no evidence of differences in maternal FOC in patients with preceding major traumas when compared to the control group. Therefore, it seems highly likely that the major trauma itself is the explanatory factor for the increased rate of elective CB. The incidence of fear of childbrith after major orthopedic traumas.